Anti-diabetic properties and nutrigenomic basis of Curculigo latifolia - Ishak, Nur Akmal; Ismail, Maznah (2015)
Curculigo latifolia (C. latifolia) plant grows wildly in tropical Asia especially in Malaysia. C. latifolia fruit has 9000 times the sweetness of sucrose and it is due to a protein known as curculin. This indicates that C. latifolia plants has the potential to be used as an alternative low-calorie sweetener for diabetic patients. In the present study, anti-diabetic properties of C. latifolia fruit:root and the pertinent mechanism were investigated on diabetic-induced rats. Diabetes rats were developed by feeding high fat diet (HFD) which contain 56.9% calorie contributed by fat and low dose STZ (40 mg/kg bw) injection. Rats were administered with C. latifolia fruit:root at graded oral doses 50, 100 and 200 mg/kg b.w for 30 days. Before and after treatments, blood glucose, plasma lipid and adiponectin were measured to evaluate its anti-diabetic effects. The regulatory effects of C. latifolia fruit:root extracts on genes involved in glucose and lipid metabolisms were further studied on glucose transporter (GLUT 4), peroxisome proliferator-activated receptor (PPARy) and adiponectin receptor (AdipoR1) in skeletal muscle tissue. The C. latifolia fruit:root possessed anti-diabetic activities as shown by the decreased of blood glucose, total cholesterol (TC), triglyceride (TG) and low density lipoprotein-cholesterol (LDL), as well as increased plasma level of adiponectin. Treatment with 200 mg/kg b.w of C. latifolia fruit:root extracts significantly improved glucose metabolism in diabetic-induced rats compared to other concentrations by increased gene expression of GLUT 4 (3 fold) and PPARy (4 fold) tissue in. Furthermore, adipose it also improved lipid metabolism by increased the expression of AdipoR2 (3 fold). Based on the current findings, C. latifolia fruit:root extracts exhibit anti-diabetic properties on hyperglycemia and hyperlipidemia in diabetic rats possibly through regulating the levels of GLUT4, PPARy and AdipoR2 tissue. Findings also provide an opportunity to food industries in designing product for diabetic complications.